Comparison among single-phase test, automated screening method and GC/MS for the traceability of ketamine in urine - Alice Visione; Giovanni Michele Lagravinese (Epidemiology, Biostatistics and Public Health)
BACKGROUND The use of ketamine, for non-medical purpose, results widespread also in Italy. This drug is not searched by institutional centers, charged of the responsibility to realize the execution of toxicological analysis based on the article 187 of The New Italian Highway Code. We evaluated the reliability of the single-phase test comparing it with an automated screening method and a gas chromatography-mass spectrometry to search the presence of ketamine on casualty patients involved in car accidents in Rome. METHODS The screening analysis were performed by a single-phase test (with a cut-off settled at 1000 ng/ml), and an automated immunoenzymatic assay (cut-off settled at 330 ng/ml). The confirmation tests have been realized by gas chromatography-mass spectrometry. RESULTS The single-phase test highlighted ten positive samples out of 294. The automated instrument confirmed only six out of ten previous positive samples, meanwhile the instrument found further four positive samples, considered negative by the single-phase test. The presence of ketamine is confirmed by gas chromatography-mass spectrometry only in seven samples out of fourteen resulted positives from both screening analysis. Three samples out of seven confirmed by gas chromatography-mass spectrometry were positive only to ketamine. CONCLUSION Following the law indications, ketamine is not searched: this limit does not make the authorities able to apply the penalties expected for road laws violations. The automation is essential to guarantee the reliability of toxicological screening tests, especially to medico-legal significance. This results highlight the absolutely necessity of the execution of the confirmation test, successively to screening analysis.